Formulation and realization of a computing experiment for unsteady and nonlinear problems of a solid fuel rocket engine - Egorov, M.Y.; Egorov, S.M.; Egorov, D.M.; Mormul, R.V.; Panferov, A.Y. (Perm Federal Research Centre Journal, 2017)
In order to optimize the parameters of a rocket engine on solid fuel (and other technical systems on solid fuel) an attempt of a direct numerical simulation of its intrachamber processes is made. The adjoint formulation of the problem is considered. Each of the subtasks is considered in interrelation with the others and resolved simultaneously - at one step in time. To solve the given problem a set of applied programmes has been developed on a computer that uses the OpenCL standard of multithreading information processing. The results of numerical calculations are given.